Analysis of the Literary Traditions of Zolāli Khānsāri’s Hosne Galusouz Masnavi through the Poet's New and Innovative Images - Somayeh Mazharisefat; Mahindokht Farrukhnia; Behjat-sadat Hejazi (مطالعات زبانی و بلاغی)
One of the important factors in determining the style and artistic values ​​of a poet's words is the way he/she uses literary traditions and conventions as well as his/her level of innovation. Some poets of Indian style, while benefiting from literary traditions, have also tended to change them. Zolāli Khānsāri, an Indian style poet in the 17th century AD (11th century AH/10th century SH), is among those poets both following tradition and making innovation. This descriptive-analytical research examines and evaluates the images in one of Zolāli Khānsāri’s Masnavis, titled Hosne Galusouz, from the perspective of literary traditions. According to the findings of this research, the literary traditions of this masnavi are mainly the topics related to human, the sky and its related elements, the four elements, flowers and plants, and the sea and its related elements. The way Zolāli Khānsāri benefits from these traditions in Hosne Galusouz's demonstrates that the most frequent form of following literary traditions as well as novelty and innovation has occurred in the topics related to human and the sky and its related elements. In addition, the results of the present study shows that Zolāli Khānsāri, while following literary traditions, has placed himself in the ranks of innovative poets and has even influenced poets such as Sā'eb Tabrizi and Bidel Dehlavi by creating new and innovative images.